Biomechanical effects of augmented ankle power output during human walking - Fickey, S. N.; Browne, M. G.; Franz, J. R. (The Journal of Experimental Biology, 2018)
The plantarflexor muscles are critical for forward propulsion and leg swing initiation during the push-off phase of walking, serving to modulate step length and walking speed. However, reduced ankle power output is common in aging and gait pathology, and is considered a root biomechanical cause of compensatory increases in hip power generation and increased metabolic energy cost. There is a critical need for mechanistic insight into the precise influence of ankle power output on patterns of mechanical power generation at the individual joint and limb levels during walking. We also posit that rehabilitative approaches to improve locomotor patterns should consider more direct means to elicit favorable changes in ankle power output. Thus, here we used real-time inverse dynamics in a visual biofeedback paradigm to test young adults' ability to modulate ankle power output during preferred speed treadmill walking, and the effects thereof on gait kinematics and kinetics. Subjects successfully modulated peak ankle power in response to biofeedback targets designed to elicit up to ±20% of normal walking values. Increasing ankle power output alleviated mechanical power demands at the hip and increased trailing limb positive work, propulsive ground reaction forces and step lengths. Decreasing ankle power had the opposite effects. We conclude that ankle power generation systematically influences the workload placed on more proximal leg muscles, trailing leg mechanical output and step length. Our findings also provide a promising benchmark for the application of biofeedback to restore ankle power in individuals with deficits thereof due to aging and gait pathology.